Corrosive Behavior and Physic-Chemical Characterization of Filtration Tanks - Casanova-del-Angel, Francisco (Scientific Research, 2017)
Most drinkable water supplied to the public in Mexico City comes from deep wells which extract water from the subsoil. Before being distributed, it is treated in steel filtration tanks. This water must be subject to evaluation through physic-chemical and bacteriological analyses in order to determine its quality. However, doubts always remain over the influence of the components of this water on the corrosive behavior of the filtration tanks. In light of this, this article studies the physic-chemical characterization values of water and presents the results. This has also enabled the analysis of the corrosion speed of filtration tanks components, boilers and water-cooled systems, where incrustations in pipes, obstructions and loss of heat transfer efficiency occur, rendering drinkable water bad tasting and, after some time, causing pitting corrosion although this type of corrosion only causes serious problems in the long term.
Keywords: Corrosion Speed; Steel; Spectrometry; Damage by Corrosion; Physic-Chemical Characterization